Teacher Education for Rural Schooling-A Status Report - Murry R Nelson (Journal of Research in Rural Education, 1983)
This paper describes the results of a survey of 56 universities, from states with large rural populations, to assess their offerings of teacher training programs designed specifically around the needs of rural educators. While the responding schools acknowledged that large proportions of their graduates found employment in rural schools, the delivery of courses and programs does not always reflect that fact. Description of needs, implications, and suggestions for teacher training for rural settings are made.